Sejarah Pabrik Gula Modjopanggoong Sebagai Roda Ekonomi Abad 20 - Junianto, Dwi; Hendriani, Dita (El Tarikh : Journal of History, Culture and Islamic Civilization, 2020)
This study aims to examine the historical side of the Modjopanggoong Sugar Factory, the development of productivity as indicated by the yield produced and the contribution of economic activity. The Modjopanggoong Sugar Factory located in the village of Kauman Tulungagung was established since the Dutch East Indies Government has experienced the dynamics of historical ups and downs. The research methods used by literature study are collected through documents, books, magazines and historical stories. The existence of this sugar factory has remained strong until now and operates a steady milling with an installed capacity of 2800 tons of sugar cane per day. Throughout the long history of revitalization activities in order to get the effectiveness and efficient operations. Of course, full support from sugar cane farmers as partners is an important asset that is continuously intertwined in the long run. The presence of a sugar factory also contributes to employment which is not only economic but also a sugar product as a renewable energy source.Keywords: Sugar Plant History, Cane Farmer, Rendemen.